Accessing Transgender // Desiring Queer(er?) Archival Logics - Rawson, K.J. (Archivaria, 2010)
While efficient and satisfactory access may be a common goal for most archives, it is rarely achieved in full. In this article, the author considers specific access barriers for both transgender patrons and transgender materials within archives. In particular, the author argues that environment and language shape the ways in which patrons encounter archives and the materials contained therein. Rather than seeking satisfactory access, the author suggests that deferred or denied satisfaction might also produce productive encounters for archival researchers. RÉSUMÉ Bien que l’accès efficace et adéquat demeure un but commun pour la plupart des institutions d’archives, il n’est que rarement atteint complètement. Cet article se penche sur des obstacles spécifiques qui empêchent l’accès aux utilisateurs transgenres et aux documents transgenres dans les archives. L’article affirme que l’environnement et l’usage de la langue influencent les façons dont les utilisateurs approchent les archives et les documents qui y sont conservés. Plutôt que de promouvoir un accès adéquat, l’article suggère que la satisfaction reportée ou refusée peut aussi produire des expériences enrichissantes pour les chercheurs aux archives.